Ecclesiologia dal Vaticano II: Un Concilio su Dio o sulla Chiesa? - Pasquale, Gianluigi (Rassegna di teologia, 2017)
At the start of the Second Vatican Council (1962-1965) the objective of the council members was not entirely clear. The Church needed at this time to speak in more understandable terms about God. Fifty years after the publication of this miscellaneous volume in honour of Cettina Militello there are no doubts: in reflecting on God the Church sought to renew herself, with a dynamism that ecclesiology records and promotes as it would any other theological treatise.